1998
DOI: 10.1007/bf02475355
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of catalytic oxidation of aqueous sodium sulfite

Abstract: A gas-lift bubble column was used to investigate the kinetics of the reaction between oxygen and aqueous solutions of sodium sulfite in the presence of cobalt sulfate catalyst. Reaction orders have been determined for the ~dfite, catalyst, and oxygen under high and low oxygen partial-pressure conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…In order to further test the validity of the proposed fastreaction regime assumption, it is necessary to check the value of ffiffiffiffi ffi M p , and according to eqn (11), we can obtained the following equation: 17,19 ffiffiffiffiffi…”
Section: General Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further test the validity of the proposed fastreaction regime assumption, it is necessary to check the value of ffiffiffiffi ffi M p , and according to eqn (11), we can obtained the following equation: 17,19 ffiffiffiffiffi…”
Section: General Oxidationmentioning
confidence: 99%
“…These studies oen experimentally investigate the effects of operation parameters, such as air ow rate, S(IV) concentration, pH, oxygen partial pressure, and temperature on the oxidation rate of S(IV) by bubbling air into S(IV)-loaded solution. For instance, Shaikh et al 17 studied the heterogeneous oxidation of aqueous sodium sulte in the presence of cobalt sulfate as the catalyst, and found that the reaction rate was pseudo-zero-order and rst-order with respect to sulte concentration and catalyst, respectively, while the reaction was rst-order with respect to above a critical oxygen partial pressure, second-order in below a critical oxygen partial pressure. As for the sulte oxidation in magnesium-based wet FGD process, Shen et al 11 researched the kinetics parameters of sulte oxidation using a stirred bubbling reactor, indicating a 0.88-order in magnesium sulte, and that diffusion of oxygen was the controlling step of the oxidation process.…”
Section: Introductionmentioning
confidence: 99%
“…2 Na 2 SO 4 ð1Þ that requires cobalt nitrate Co(NO 3 ) 2 as catalyst and is pH dependent [11]. Shaikh and Zaidi [12] reported that the reaction rate is directly proportional to the concentration of the catalyst (cobalt sulphate in their experiments). They also reported that the reaction activation energy is 41.3 kJ/mol, and that the catalyst may significantly lower this activation energy.…”
Section: Introductionmentioning
confidence: 99%
“…Although this can be connected with the presence of H 2 SO 4 in Colima gases, oxidation of the sulfite ion SO 3 2− in the alkaline solution obviously occurred, obscuring the real concentrations of sulfuric acid in the gas. The sulfite ion can readily undergo oxidation in an alkaline solution [e.g., Linek and Mayrhoferova , ; Sivaji and Murty , , and references therein], especially in the presence of transition metal ions [ Huie , ; Shaikh and Zaidi , ]. Such transition metals (Fe, Co, and Cu) are available directly from fumarolic gases on degassing domes [ Allen et al ., ; Taran et al ., ], including Bezymianny (supporting information Table S4).…”
Section: Introductionmentioning
confidence: 99%